(untitled) (RuMoRes, 2023)
This paper outlines methodological considerations regarding the film discourse analysis and its dialogue with media criticism, both understood as a set of values and procedures that inform our evaluation of certain aspects of a given film. It highlights the choosing process and ends by deconstructing an excerpt from the documentary Juízo (2008), arguing on how the fictionalized inclusion of the young defendant’s face problematizes and complexifies the stigma placed upon the young offender.